Automated robot-assisted assessment for wrist active ranges of motion. (September 2019) - Zhang, Mingming; McDaid, Andrew; Zhang, Sihui; Zhang, Yanxin; Xie, Sheng Q.
Highlights: This study proposed a new assessment technique with admittance control for measuring active ranges of motion of wrists. The robotic system has a reconfigurable handle structure that allows for multi-dimensional wrist motions. The reliability was validated on 11 subjects by measuring wrist flexion/extension and radial/ulnar deviation. Abstract: The measurement of wrist active range of motion (ROM) is essential for determining the progress of hand functional recovery, which can provide insight into quantitative improvements and enable effective monitoring during hand rehabilitation. Compared with manual methods, which depend on the experience of the therapist, the proposed robot-assisted assessment technique can measure active ROM of human wrists. The robot with a reconfigurable handle design allows for multiple wrist motions. Experiments were conducted with 11 human subjects to measure ROMs of human wrist flexion/extension and radial/ulnar deviation. Reliability analysis was conducted by calculating the intra-class correlation coefficients (ICC), standard error of measurement (SEM) and SEM%. Results showed high reliability (ICC2, 1  ≥ 0.89, SEM ≤ 2.36°, SEM% ≤ 6.81%). Future will focus on adaptive joint self-alignment design between human users and robots to further improve its assessment accuracy.